The Impact of Minimum Wages on Teenagers' Educational Expectations - Pascal Heß; Silke Anger; Max Kunaschk (ZBW - Leibniz-Informationszentrum Wirtschaft, 2019)
We study the effect of the introduction of the German statutory minimum wage law in 2015 on teenagers' educational expectations. We focus on low-skilled students, the group most likely to be affected by the minimum wage after entering the labor market. Theoretical predictions of the effect of minimum wages on educational investments are ambiguous. On the one hand, to qualify for minimum wage jobs, teenagers might try to raise their productivity through higher educational achievement. On the other hand, they face higher opportunity costs of schooling, when being exposed to the minimum wage, and therefore might decrease educational goals. To shed light on the theoretically ambiguous relationship between minimum wages and teenagers' educational expectations, we explore the effects in a Difference-in-Difference(-in-Difference) framework using rich individual level data on teenage students. We find that teenagers' educational expectations, on average, decrease with age. With respect to the minimum wage, the analyses point towards important heterogeneous effects. To control for regional variation in treatment intensity, we include the share of workers affected by the minimum wage at the state level. The results suggest that in hardly affected regions, the minimum wage did not alter expected wage or employment prospects of adolescents and hence did not affect educational plans of students. In contrast, in highly affected regions, educational expectations of teenagers increased following the minimum wage introduction. Therefore, low-skilled students seem to consider regional labor market conditions in their intended schooling decision and try to compensate for lower employment probabilities by increasing investments in human capital.
Keywords: J24; J31; I21; 330; minimum wage; educational expectations; employment prospects